Pengaruh Kualitas Produk dan Harga terhadap Minat Beli Santri Asrama Ar-Raudhoh Cetakan Toko At-Tazkiyah HM Al-Mahrusiyah Lirboyo Kota Kediri - Maharani, Luviana; Mala, Iva Khoiril; Sutantri, Sutantri (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of quality and price on buying interest of As-arroudho lirboyo Kediri students. The book is one of the most important needs for students. Sehimgga kitab itself is also a product that is always needed by students. The method used in this research is a quantitative method. Quantitative research is research conducted by collecting data from a list of structured questions (questionnaire). Data collection techniques by distributing questionnaires, and observation. While analyzing the data using validity and reliability tests and normality and homogeneity followed by kendall tau correlation: 1) quality has an effect on buying interest with the results obtained a value of 0.726 with a significance of 0.346. This means that 0.726 <0.05 so it can be concluded that the hypothesis has a very high significance relationship. And quality there is an influence between the two variables. 2) price on buying interest with the results obtained a value of 0.709 with a significance of 0.379. This means that 0.709 <0.05 so it can be concluded that the hypothesis is accepted and the price has an effect on the students' buying interest in the alfiyah book in the At-Tazkiyah lirboyo kediri shop. 3) The results of the correlation test show that the two variables quality and price have an effect on buying interest. This is indicated by the quality variable (X1) in the alfiyah book printed by the At-Tazkiyah store obtained a value of 0.726 with a significance of 0.346. This means that 0.726 <0.05. While the variation variable (X2) in the printed alfiyah book of the At-Tazkiyah store obtained a value of 0.709 with a significance of 0.379. This means that 0.709 <0.05 So it can be concluded that the hypothesis is accepted, meaning that quality and price have an effect on santri buying interest in the alfiyah book in the At-TAzkiyah Al-mahrusiyah shop in Lirboyo Kediri City. Keywords: Farming, Oil Palm, Revenue.